Irreparable Damage: International Housing Rights and Local Housing Struggles in Rome after 2020 - Davoli, Chiara; Portelli, Stefano (PARTECIPAZIONE E CONFLITTO, 2023)
The recent interventions of the UN High Commissioner of Human Rights (OHCHR) to suspend evictions of tenants in Rome, Italy, allows us to shed light into the forthcoming social catastrophe caused by Italian housing policies, and into the new advancements of social movements for housing. As two scholar-activists involved both in research on housing and in political actions to prevent evictions, we describe how housing movements in Rome are facing the contradictions between local and international discourses on the right to housing.